Examining the role of 'creative class' ideas in urban and economic policy formation: the case of Dublin, Ireland. (14th January 2011) - Lawton, Philip; Murphy, Enda; Redmond, Declan
Throughout the last decade the 'creative class' thesis has received significant attention within academic and policymaking circles. This paper analyses the role of the 'creative class' thesis within recent urban and economic policy formation in Dublin. In methodological terms, the study uses in-depth analysis of recent policy documents which is supplemented by interviews with key stakeholders involved in the formulation and implementation of policy at various scales. The paper argues that weaknesses in the structure of local government and current fiscal rectitude in Ireland combined with the flexible nature of Florida's 'creative class' ideas have ensured its easy adaptability as 'fast policy'. Here we focus on two particular areas of policy formation: 'place-making' and the formation of new networks of power. We contend that the shortcomings of this approach are based on the lack of causal evidence linking the promotion of a 'vibrant place' with economic prosperity and the lack of democratic accountability within the formation of networks of elite actors.